Does integrated reporting quality matter to capital markets? Empirical evidence from voluntary adopters - Luca Leukhardt; Michel Charifzadeh; Fabian Diefenbach (Corporate Social Responsibility and Environmental Management, 2022)
This study examines the relevance of integrated reporting quality (IRQ) to capital markets. We investigate whether IRQ benefits capital market participants by improving a firm's information environment, using analyst earnings forecast accuracy as a proxy. Our study focuses specifically on companies that publish integrated reports on a voluntary basis. Based on a scoring model, we assess IRQ and its effects with data from 2015 to 2019 of 101 companies. The results indicate no significant relationship between IRQ and analyst earnings forecast accuracy. Thus, IRQ does not appear to improve a firm's information environment, at least not currently in a voluntary setting. Drawing on previous literature in the field, this study further concludes that integrated reporting (IR) in general has not yet reached its full potential in benefitting capital markets. Potential implications of our results are that the standard setters should work to improve the specificity and rigor of their guidelines, and analysts should become more involved in developing IR guidelines to make them more relevant to their information needs. IR seems to unfold its benefits better in mandatory settings, which could call for regulators to make IR mandatory.
Keywords: 650; forecast accuracy; forecast error; information environment; integrated reporting; integrated reporting quality; sustainability reporting; voluntary disclosure